IMPROVING USE RESTRICTION WITH MODIFIED ATTRIBUTES BASED ALGORITHMS - Kobiljanov Sh. N. (Ecomind Press, 2026)
This in the article commerce banks information in the system use restriction in the process information quality and system resources between integration effective to manage SMART-Q (Systematic Multi-layered Algorithm for Real-Time Quality ) algorithm offer Algorithm bank information in systems there is was different information sources only quality criteria based on real time in mode analysis to do , to check and integration opportunity The SMART-Q algorithm gives of information completeness , accuracy and compatibility automatic evaluation , various in format information only structure based on combine and information quality decrease prevent to take service does . Proposal done approach commerce banks information in systems security increase, errors reduce and use restriction in the process decision acceptance to do efficiency provision opportunity gives.
Keywords: Commerce banks , information system , usage restriction , data quality, integration , SMART-Q algorithm , real -time mode , information safety.